Strategi Sekolah dalam Pencegahan dan Penanganan Anti-Bullying di SDN Kalangsemanding Jombang - Muzayana, Muzayana; Khoirur Roziqin , Muhamad (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This research aims to analyze the strategies implemented by SDN Kalangsemanding Jombang in preventing and handling bullying cases. The research method used is qualitative with a case study approach. Data collection was carried out through observation, interviews, and documentation. Data analysis was performed using interactive analysis techniques. The results show that the strategies implemented by the school include three main aspects: preventive, intervention, and rehabilitative strategies. Preventive strategies involve anti-bullying outreach, strengthening religious values, and implementing strict disciplinary rules. Intervention strategies include counseling for victims and perpetrators, as well as conflict resolution based on mediation. Rehabilitative strategies focus on psychological support and character development to change student behavior. It can be concluded that the combination of strategies implemented at SDN Kalangsemanding Jombang is effective in reducing bullying cases. This research recommends strengthening supervision and increasing the involvement of parents and the school community.